(untitled) (Current Horticulture, 2024)
Present days’ farming is not sustainable in consonance with economics, ecology, equity, energy and socio cultural dimensions. Indiscriminate use of chemical fertilizers, weedicides and pesticides, especially in fruit production has resulted in various environmental and health hazards along with socio-economic problems. Grower community is trying to find out an alternative sustainable farming system, which is ecologically sound and economically and socially acceptable. Sustainable production is unifying concept, which considers ecological, environmental, philosophical, ethical and social impacts, balanced with cost-effectiveness. Traditional organic production practices, which are based on natural and organic methods of farming offer several effective, feasible and cost-effective solutions to most of the basic problems being faced in conventional production of fruit crops. Organic fruit cultivation helps in climate mitigation, carbon fixation, soil fertility improvement and water conservation. In present scenario, shifting from conventional to organic, maintenance of soil health and insect pest management will be major challenges which can be taken care of with adaptation of complete organic package of practice in fruit production.